SWOT Analysis of Micro, Small and Medium Enterprises in Rural Society: A study conducted in the Ganjam District of Odisha - Das, Mrs. Manju Prava (International Journal of Scientific Research and Management (IJSRM), 2017)
Micro, Small and Medium Enterprises (MSME) play vital role in the process of development. It generates employment at low cost and helps the society to move on the path of prosperity & growth. As more than 65% of Indians live in villages and as there is little scope for establishment of Large-scale industries in these areas, MSME is an important aspect with regard to development of rural areas. The State of Odisha is one of the states of India filled with heavenly natural resources. The irony is that despite of being rich in natural resources particularly in rural areas, it is still one of the backward states in industrialization. Even though the State has huge potential for industrialization, especially for MSME sector, its potential has not been fully harnessed so far. Thus the present paper is an attempt towards finding out the Strengths, Weaknesses, Opportunities and Threats of MSMEs in Rural Society of Odisha. The study is conducted in the District of Ganjam, which is one of the coastal districts of the state. At the end, some suggestions by which the challenges of threats can be reduced are recommended.